The Relevance of Al-Naḥw Al-Asāsī and Al-Naḥw Al-Taṭbīqī to Modern Arabic Grammar Instruction: A Comparative Textbook Analysis - Muhamad Rizki Sahriya Ramadan; Zaki Ghufron; Mufrodi Mufrodi (KURAS Institute, 2026)
This study aims to compare the content quality, language, presentation, exercises, graphical design, and pedagogical relevance of Al-Naḥw al-Asāsī and Al-Naḥw at-Taṭbīqī to identify their respective strengths and suitability for modern Arabic grammar instruction. Using a qualitative approach with comparative content analysis, the study evaluates both textbooks based on a synthesis of Mudzakkir’s and Cunningsworth’s textbook evaluation frameworks, focusing on five aspects: content, language, presentation, exercises, and graphics. The findings indicate that Al-Naḥw al-Asāsī excels in content depth, systematic organization, and grammatical accuracy, making it particularly suitable for academic and theoretical studies. Meanwhile, Al-Naḥw al-Taṭbīqī demonstrates strengths in language accessibility, inductive presentation, contextualized exercises, and learner-friendly design, making it more compatible with contemporary learner-centered approaches. The study concludes that the two textbooks are complementary rather than competitive, as they represent different instructional orientations: theoretical mastery and practical language application. Integrating the strengths of both textbooks may contribute to more effective and relevant naḥw instruction for contemporary Arabic language learners.